Implementation of OpenStack as a Private Cloud Infrastructure Solution to Support Information Technology-Based Learning - Dayu Destamy Ariefin; Ivan Hanafi; Muhammad Rifán (PT. Anagata Sembagi Education, 2025)
The rapid development of information technology has transformed the educational landscape, particularly through the integration of cloud computing. OpenStack, an open-source platform for private cloud infrastructure, offers high flexibility and full control over IT resources, making it a promising solution for educational institutions. This study explores the implementation of OpenStack to support technology-based learning by conducting a literature review of recent academic publications. The findings highlight several benefits of using OpenStack in education, including improved efficiency in managing digital resources, enhanced students' practical skills through hands-on experiences, and reduced operational costs. These advantages position OpenStack as a valuable tool in promoting digital innovation in schools and universities. However, the study also identifies key challenges, such as infrastructure limitations and the complexity of system management, which may hinder broader adoption. Despite these obstacles, OpenStack's scalability and open-source nature provide educational institutions with opportunities for customization and long-term development. In conclusion, OpenStack presents considerable potential as a foundational platform for digital transformation in education, aligning with the growing demand for flexible, cost-effective, and sustainable technological solutions. Future research is recommended to explore best practices, implementation models, and collaborative strategies that can enhance the adoption and effectiveness of OpenStack in diverse educational settings.